Search for CP violation in the decay D+→π−π+π+ - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Hansmann-Menzemer, Stephanie; Jäger, Andreas; Kreplin, Katharina; et al. (Physics letters, 2014)
A search for CP violation in the phase space of the decay D+→π−π+π+ is reported using pp collision data, corresponding to an integrated luminosity of 1.0 fb−1, collected by the LHCb experiment at a centre-of-mass energy of 7 TeV. The Dalitz plot distributions for 3.1×106 D+ and D− candidates are compared with binned and unbinned model-independent techniques. No evidence for CP violation is found.
Im Titel sind die Plus- und Minuszeichen hochgestellt
Available online 17 December 2013
LHCb Collaboration: R. Aaij, S. Bachmann, A. Bien, M. De Cian, A. Di Canto, F. Dordei, C. Färber, E. Gersabeck, L. Grillo, S. Hansmann-Menzemer, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, S. Wandernoth, D. Wiedner, A. Zhelezov [und weitere]
Gesehen am 05.11.2020